A detailed structural analysis, morphological and optical study of Mg-Zn nano ferrite. (2023) - Kumari, Sonam; Thakur, Preeti; Singh, Satyendra; Thakur, Atul
Abstract: Mg-Zn nanoferrite with the composition of Mg0.4 Zn0.6 Fe2 O4 was prepared using the citrate precursor process. Detailed structural analysis was performed on Mg-Zn nanoferrite to calculate crystallite size, lattice constant, X-ray density, bulk density, and porosity using XRD data. Also, the strain on the sample was calculated by plotting Williamson – Hall (W-H) plot. Scanning electron microscopy (SEM) and Fourier transform infrared spectroscopy (FTIR) were performed to study morphological and optical properties. The spinel structure was confirmed by XRD with a crystallite size of 38 nm. SEM micrograph of the sample showed almost spherical-shaped nanoparticles. FTIR spectra disclosed two characteristic bands showing tetrahedral (A) and octahedral (B) site occupancies. Under UV–visible light irradiation, photocatalytic degradation of rhodamine B dye and the degradation efficiency is obtained to be 70 % in 60 min. Therefore, it is concluded that Mg0.4 Zn0.6 Fe2 O4 is a promising material for water purification.